Determinants of Islamic Bank Market Capitalisation: The Moderating Role of Banking Growth in the MENA Region - Rahman, Taufikur; Arinta, Yusvita Nena; Rahmayanti, Dini; Nurhadi, Bayu (Universitas Muhammadiyah Magelang, 2025)
Market Capitalisation is an important market indicator of the value of a company's shares. This study aims to analyze the role of banking growth in the relationship between the educational background of Islamic Supervisory Board (ISB) and market capitalism of Islamic banking in the Middle East and North Africa (MENA) region. The samples of this research are 183 Islamic banks in the Middle East and North Africa (MENA) region. Data was obtained from the ESGI database. The method used is Ordinary Least Squares and MRA to test the relationship between ISB educational background and market capitalisation and the role of banking growth as a moderating variable. The results show that the ISB educational background positively affects the market capitalisation of Islamic banks in the MENA region and the banking growth has succeeded in strengthening this effect. These findings offer insight to consider in establishing an Islamic supervisory board with a high educational background so that investor confidence becomes stronger in choosing their investments. These findings show the importance of a method of governance, transparency, and responsibility that an Islamic supervisory board must have so that its knowledge is appropriate to its field.